Pendidikan Berbasiskan Media dan Modul - Hidayat, Syarif (Al-Riwayah : Jurnal Kependidikan, 2020)
Instructional media selection includes several criteria that influence each other. The criteria are different according to the curriculum, learner analysis, a condition that occurs when planning and other variables. Environment, situation or condition, time and tolerance impact of the use are also very influential in determining the criteria for the selection of media. Selecting the media for learning should consider criteria: a) The accuracy of the learning objectives, b) Support for the contents of the learning material, c) Ease of obtaining media, d) Teachers’ skills in using, e) Time available for use, and f) In accordance with the level of students’ thinking. Good learning media must meet several requirements. Instructional media should increase the motivation of learners. The use of media has the goal to motivate learners. In addition, the media should stimulate learners remember what they have learned in addition to providing new learning stimuli. Good media enable learners to provide responses, feedback and also encourage students to do the practices correctly. This paper attempts to describe the role and the function of media and modules in the learning process with learners.